2005
DOI: 10.1002/ana.20532
|View full text |Cite
|
Sign up to set email alerts
|

6‐Pyruvoyl‐tetrahydropterin synthase deficiency with mild hyperphenylalaninemia

Abstract: Severe 6-pyruvoyl-tetrahydrobiopterin synthase deficiency is a tetrahydrobiopterin deficiency disorder that presents in infancy with developmental delay, seizures, and abnormal movements associated with hyperphenylalaninemia usually detectable by neonatal phenylketonuria screening programs. We describe an 8-year-old girl with delay, seizures, and dystonia with mild hyperphenylalaninemia detected in late childhood. The diagnosis of 6-pyruvoyl-tetrahydrobiopterin synthase deficiency was made by analysis of pteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The combined treatment with Sapropterin dihydrochloride and L-DOPA/Decarboxylase inhibitor improved the clinical manifestations of our patients, consistent with the results of other studies [ 5 , 30 , 31 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…The combined treatment with Sapropterin dihydrochloride and L-DOPA/Decarboxylase inhibitor improved the clinical manifestations of our patients, consistent with the results of other studies [ 5 , 30 , 31 , 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…In comparison, NBS was negative in two cases of PTPSD. However, retrospective re-evaluation revealed that the analysis was most likely done by the semiquantitative bacterial inhibition assay (Guthrie method), known to cause falsenegative results [43,44]. In PCDD, all reported cases presented with HPA.…”
Section: Key Diagnostic Test: Newborn Screeningmentioning
confidence: 99%
“…This is an unusual finding in PTPS deficiency, only rarely reported to date. [14][15][16] These observations suggest the possible existence of a third form of PTPS deficiency (''central-only''), which may elude newborn screening for hyperphenylalaninemia.…”
Section: Discussionmentioning
confidence: 99%